Tingkat Kemandirian Belajar Pada Remaja - Anisa Fitriani; Fadhilla Yusri (Consilium : Berkala Kajian Konseling dan Ilmu Keagamaan, 2022)
The purpose of this research is to see how much the level of learning independence in adolescents in Jorong Koto Nan Gadang, Kenagarian Aie Angek, X Koto District, Tanah Datar Regency. The research methodology uses descriptive quantitative with a population of all adolescents, amounting to 40 people. While taking the sample using a sampling technique, with research instruments using a Likert scale with 39 statement items that are already valid and using percentage descriptive analysis techniques. The results of research indicators are: an indicator of independence from others is 78% which is a high category, the indicator has self confidence is 75% which is a medium category, the indicator of disciplined behavior is 73% which is a medium category, the indicator has a sense of responsibility is 75% which is a medium category, the indicator of behavior based on self-initiative is 67% which is as a medium category, and the indicator of self-control is 68% which is medium category. While the percentage of adolescent learning independence level as a whole is 72,7% in the medium category. Ideally, adolescent to be independent in learning if they reach the high or very high category, which is between 76-100%.